The American Heritage dictionary of science - Barnhart, Robert K.; Steinmetz, Sol. (Boston : Houghton Mifflin, 1986)
On cover: More than 16,000 authoritative, up-to-date entries in all fields from astronomy to zoology.
Originally published: Hammond Barnhart dictionary of science. Maplewood, N.J. : Hammond, c1986.
Young Adult
Keywords: Science -- Dictionaries; Science -- Dictionaries